RECONSTRUCTION THE MEANING OF INTENTION TOWARDS BEHAVIORAL CHANGE IN ISLAMIC PSYCHOLOGICAL PERSPECTIVES - Ru'iya, Sutipyo (Journal of Islam and Science, 2021)
Aligning intentions in the Islamic view is a must because whether or not human deeds are accepted depends on their intentions. This article highlights how intentions from an Islamic perspective and how intentions arise from a psychological perspective. This research is librarian research that collects data by reading books, journals, and several relevant documents to the theme of the study. The data were obtained, then analyzed, analyzed, compared, then took the topics and cited them. According to the Islamic view, the results showed that the Intention is very urgent and should rest for the value of dedication to Allah. A sincere intention, because of Allah, will add extra strength to someone to do a job. Meanwhile, according to psychology, Intention is influenced by three things: attitude toward control, subjective norms, and perceived behavior control. The article concludes that the Intention is influenced by two things, the earthly and religious elements. Man's motivation to do work is what colors his Intention, whether for the world or the hereafter.